The Rebbe the life and afterlife of Menachem Mendel Schneerson - Heilman, Samuel C.; Friedman, Menachem (Princeton, NJ : Princeton University Press, 2010)
A biography of Rabbi Menachem Mendel Schneerson that discusses his childhood in Russia, education in Germany and Paris, messianic conviction, religious leadership, legacy, and other related topics.
Farbrengen : the gathering of the emissaries -- Death and resurrection -- Coming of age in a time of transition -- Entering the court of Lubavitch -- From survival to Uforatzto -- On a mission from the Rebbe in life -- From resurrection to death : we want moshiach now -- On a mission from the Rebbe in his afterlife.
Includes bibliographical references (p. 283-329) and index.
Description based on print version record.
Keywords: Schneerson, Menachem Mendel, -- 1902-1994.; Rabbis -- New York (State) -- New York -- Biography; Hasidim -- New York (State) -- New York -- Biography; Habad; Electronic books; RELIGION / Judaism / General